The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1093/ndt/17.4.614
|View full text |Cite
|
Sign up to set email alerts
|

Radiological placement of the AshSplit haemodialysis catheter: a prospective analysis of outcome and complications

Abstract: Radiological insertion of the AshSplit catheter is well tolerated, providing reliable short- and long-term dialysis access. Radiology also has a role in maintaining patency. As with all tunnelled catheters, infection remains a problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
2
18
1
Order By: Relevance
“…Mean AshSplit catheter duration (246 days) is similar to Permcath (239 days) in our group, but is longer than previously reported, 190 days for AshSplit, [2] 105 days for Permcath, [4] and 199 days for Tesio catheters. [12] As some of our catheters still functioned after 1,278 days, they could be considered as permanent vascular access, and therefore, our catheter dwell times are approaching that of the gold standard native AVF.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Mean AshSplit catheter duration (246 days) is similar to Permcath (239 days) in our group, but is longer than previously reported, 190 days for AshSplit, [2] 105 days for Permcath, [4] and 199 days for Tesio catheters. [12] As some of our catheters still functioned after 1,278 days, they could be considered as permanent vascular access, and therefore, our catheter dwell times are approaching that of the gold standard native AVF.…”
Section: Discussionsupporting
confidence: 76%
“…This fact stresses the importance of maintaining a safe and effective method of insertion, with few complications. Insertion complications experienced for AshSplit (6%) and Permcath (6%) in our study group are lower than previously reported by Ewing et al (11.8% AshSplit) [2] and Perini et al (Tesio 9%), [11] with only one patient requiring further intervention as a result of a complication (0.5% overall).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This meta-analysis of internal jugular TDC-related bacteremia rates was based on data published in 15 articles that met the following criteria: prospective studies, including prospective cohort and randomized controlled trials of tunneled, cuffed catheters with at least 20 patients. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Studies of the LifeSite Hemodialysis Access System (Vasca Inc, Tewksbury, Mass) and Dialock Access System (Biolink Inc, Norwell, Mass) were excluded. The final normalized cumulative TDC bacteremia control rate was 2.3/1000 catheter days.…”
Section: Methodsmentioning
confidence: 99%
“…Catheter dysfunction has been defined by Kidney Disease Outcomes Quality Initiative (K/DOQI) guidelines as "failure to maintain an extracorporeal blood flow sufficient to perform hemodialysis without significantly lengthening the hemodialysis treatment" (4). The guidelines and many research studies set a minimum blood flow target of 300 ml/min (5)(6)(7)(8)(9)(10)(11). Using this target, between 55 and 87% of catheters will experience dysfunction at least once (6,12), and 5 to 13% will require catheter replacement to treat dysfunction that is refractory to other measures such as patient repositioning, saline flushes, lumen reversal, and thrombolytic dwells (9 -11,13,14).…”
mentioning
confidence: 99%